Duffy antigens and hypertension in a black population. - Miller, J M (1985)
Skin color and social class have been suggested as reasons to explain the greater prevalence of hypertension in Blacks as compared to Whites. The presence of Duffy red blood cell proteins, a measure of "whiteness" in Blacks, was unrelated to the presence of elevated blood pressure in 722 Black hospital patients. The finding suggests that social class rather than skin color is associated with the greater prevalence of hypertension in Blacks.